Compressed soil blocks: Influence of fibers on flexural properties and failure mechanism. (15th September 2016) - Donkor, Peter; Obonyo, Esther
Highlights: The polypropylene fibers improved the post-crack performance of the beams. Higher peak loads were reached at fiber contents of 0.6% and 0.8%. Both fiber pullout and fracture was observed during specimen testing. Abstract: Soil blocks are sustainable, low-cost, masonry materials that exhibit low resistance to bending. This study focused on experimentally investigating the influence of polypropylene fibers on the flexural performance and failure mechanism of cement stabilized soil blocks. Specimens were produced with different fiber mass proportions for comparison with specimens without fibers. Test results showed an improvement in post-crack flexural behavior and toughness of the fiber-reinforced specimens compared to the unreinforced ones. Depending on fiber content, specimens exhibited either a deflection softening or deflection hardening behavior during testing. Failure of specimens was characterized by both fiber fracture and pullout.